Desire Revolution: Imagining Queer Europe. Issue 1 (2nd January 2021) - Anderson, Fiona; Davis, Glyn; Raha, Nat
Abstract: How might historical queer and trans activist tactics and visions of the future be used to invigorate contemporary LGBTQ+ politics and thought? This article provides an introduction to the 'Imagining Queer Europe Then and Now' special issue of Third Text, an issue which emerges from the final conference of the pan-European queer history project 'Cruising the Seventies'. We identify the uneven and complex ways in which LGBTQ+ activism, networks, erotic connections, and forms of cultural expression manifested across Europe in the 1970s, and the ways in which these intersected with anti-racist, anti-colonial, anti-fascist and feminist struggles in the same era. We argue for the excavation of the unrealised possibilities of queer pasts and futures, proposing that forms of social and erotic interaction, and aesthetic and cultural intervention, can provide fresh perspectives on the queer past and the politics of its recovery.